SUPPLY CHAIN INTEGRATION AND PERFORMANCE OF SHIPPING COMPANIES IN RIVERS STATE (European Journal of Interdisciplinary Research and Development, 2025)
This study empirically investigated the relationship between global supply chain integration and firm agility of shipping companies in Nigeria. Cross-sectional research design was adopted in accessing the study’s subjects. The population of the study consists of 216 employees of shipping companies in Nigeria. A total of 5 hypotheses were proposed and statistically tested using Spearman’s Rank Correlation Coefficient. Results indicated that the dimensions of supply chain integration such as supplier integration and customer integration were significantly related to the measures of performance; which include on-time delivery and cost efficiency. It was against this background that the study concluded that keeping closer collaboration, long-term partnership and coordination with key suppliers has been proven to enhance supply chain efficiency, on-time delivery and cost efficiency. The study therefore recommended that management of shipping companies who want to improve firm agility are encouraged to establish long-term partnership and coordination with key suppliers, as these strategies have been proven to enhance supply chain efficiency, on-time delivery and cost efficiency.